Implementasi Pengabdian pada Masyarakat melalui Pedidikan berbasis EcoMasjid (Studi kasus di kelurahan semplak kota Bogor) - Heriyansyah Heriyansyah; Moch Yasyakur; Abdul Rosid; Ancha Surya Ramadhan; Hari Prasetyo (Khidmatul Ummah: Jurnal Pengabdian Kepada Masyarakat, 2020)
The environmental crisis with its various manifestations is actually a moral crisis, because humans see nature as an object, not a subject in the universal life. So the handling of existing problems must be a moral approach. It is at this point that religion must play a role through the form of religious guidance and be realized in a real form in the daily life of mankind. In accordance with the function of its existence, mosques need to participate in preserving the environment through education and verbal preaching as well as taking real actions starting from the mosque itself. The environmental education and preaching program through this mosque is called ecoMasjid. The concept of ecoMasjid comes from two words Eco and Masjid which each have a different definition. "Eco" is taken from the word "ecology" which is a term that is closely related to ecosystems, namely a system formed by the reciprocal relationship between living things and their environment. Meanwhile, the mosque is a place of prostration. The term mosque according to syara is a place provided for prayer in it and is permanent, not temporary. So that ecoMasjid is a permanent place of worship that has concern for the reciprocal relationship between living things and their environment.